2023
DOI: 10.3390/su15139930
|View full text |Cite
|
Sign up to set email alerts
|

Place-Keeping in the Park: Testing a Living Lab Approach to Facilitate Nature Connectedness in Urban Greenspaces

Abstract: Green infrastructure, particularly public greenspaces such as urban parks, plays an important role in urban environments, and improving public participation in greenspace practices and encouraging environmental stewardship can help to address some of the challenges of greenspace governance. We identify a gap in the research as to whether participation in citizen science projects can enhance connections between people and place and encourage better community participation in the stewardship of parks and urban g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Residents can enjoy a variety of advantages from these green spaces, including purification of the air and water, preservation of biodiversity, and recreational opportunities. A positive correlation between the presence of green spaces and the well-being of urban communities has been consistently demonstrated in research (Backman et al, 2023;Bille et al, 2023;Perdigones et al, 2023;Willis & Gupta, 2023). Research has demonstrated that the presence of urban green spaces can mitigate the negative impacts of high temperatures, pollution, and inundation, while also enhancing both mental and physical well-being (Devos, 2023).…”
Section: B Urbanization and Green Area Developmentmentioning
confidence: 85%
See 3 more Smart Citations
“…Residents can enjoy a variety of advantages from these green spaces, including purification of the air and water, preservation of biodiversity, and recreational opportunities. A positive correlation between the presence of green spaces and the well-being of urban communities has been consistently demonstrated in research (Backman et al, 2023;Bille et al, 2023;Perdigones et al, 2023;Willis & Gupta, 2023). Research has demonstrated that the presence of urban green spaces can mitigate the negative impacts of high temperatures, pollution, and inundation, while also enhancing both mental and physical well-being (Devos, 2023).…”
Section: B Urbanization and Green Area Developmentmentioning
confidence: 85%
“…Involving urban communities in green area-related planning and decisionmaking processes can enhance the success of such initiatives and foster a sense of ownership, according to research (Angelidou & Psaltoglou, 2017;Gearin et al, 2023;Willis & Gupta, 2023). Community participation in these processes is influenced by various factors, one of which is the imperative to confront societal challenges and devise inventive resolutions (Gilbert, 2014).…”
Section: Perceptions Of Urban Communitiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Empirical evidence indicates that all humans have some degree of a genetically hard-wired affinity with nature [23]. Immersion in nature, whether rural or urban, actual or virtual, enhances CNS and leads to increased attentional capacity, positive emotions, and various psychological benefits to well-being [24][25][26]. Indeed, there is a growing realisation of the importance of the human-nature relationship with robust links to pro-environmental behaviour that influence not only our well-being but also our behaviour toward others and our willingness to sacrifice for them, e.g., [27][28][29].…”
Section: Connectedness To Naturementioning
confidence: 99%